PATTERNS OF SMALL ARMS PROLIFERATION IN INDIA’S NORTH-EAST: AN IN-DEPTH ASSESSMENT OF ASSAM’S SECURITY LANDSCAPE - Gohain, Monjit (International Journal of Research -GRANTHAALAYAH, 2021)
The North-Eastern region of India has historically been a hotspot of ethnic, political, and armed conflicts due to its complex socio-cultural and geopolitical environment. The region's security issues, especially those in Assam, have been made worse by the spread of small arms and light weapons, which have lowered the bar for armed conflict and put human life, social cohesiveness, and national integrity at risk. This essay examines the trends in the spread of small arms, following the origins, sources, and processes of weapon circulation throughout history. The region's porous international borders and insurgency movements are strongly associated with the origins of small weapons proliferation in Assam. In order to obtain weapons and training, ethno-nationalist insurgencies like ULFA and NSCN have traditionally maintained covert connections with terrorist organizations in Bangladesh, Myanmar, and other nearby nations. There is widespread violence and instability in Assam due to the involvement of numerous parties, including foreign arms networks and local rebel groups (Baruah, 2003, p. 79). Using a combination of historical, descriptive, analytical, and comparative methodologies, the study draws from secondary sources such as books, journals, and news stories as well as primary sources such as government papers, parliamentary debates, and speeches. The results emphasize the several factors that contribute to the spread of small guns, such as unmet regional expectations, ethnic dissatisfaction, and the socio-political marginalization of communities. The report contends that strict regulation of arms trafficking and a political reconciliation approach are necessary to address the growth of small arms (Basu, 2005, p. 112).